THE ANALYSIS OF HONEYDUE SUPPLY IN SRAGEN REGENCY - Ikhsan Aminudin; Suprapti Supardi (MEDIAGRO, 2009)
This research aimed to analyze some factors which influence the supply of honeydue in Sragen Regency and to analyze the elasticity supply of honeydue in Sragen Regency. The basic method used in this research is the descriptive analysis. The research location is chosen purposively, namely in Sragen Regency. Whereas the kind of data used in this research is secondary data of time  series  during 16 years since 1990 -  2005. The correlation between the supply of honeydue and some influenced factors is formulated into lag model which is distributed into Nerlove model approach. From the result is of analysis. obtained the value of coefficient correlation (R2) is 0,87 and adjusted R2 is 0.79. From value of F test, is (0,001) significant with level of trust 95 %. The result of analysis at t test shows that variable price of honeydue at previous year, price of TSP fertilizer at year t and honeydue production at previous year are variables which have obvious influence toward the supply of honeydue in Sragen Regency. Whereas variable price of water melon at previous year, rainfall and water melon production at previous year don't give  obvious influence toward the supply of honeydue in Sragen Regency. The result of t test, obtained function model of honeydue supply in Sragen Regency as follow: Qt = 3716,109 + 21,358 Pmt-1 + 0,834 Pst-1 + - 16,46  Pttsp + 0,365 Wt + 0,483  Qmt-1 + - 0,092 Qst-1. Based on the most influence value of coefficient regression partial, variable price of honeydue at previous year is the highest one. So this variable has the biggest influence toward the supply of honeydue in Sragen Regency. The  elasticity of honeydue supply in long terms is more elastic than those in short terms.